1989
DOI: 10.1271/bbb1961.53.3233
|View full text |Cite
|
Sign up to set email alerts
|

Serum and egg antibody responses in chickens to Escherichia coli.

Abstract: The effects of Freund's adjuvants on antibody production in chickens against E. coli whole cells were examined. The levels of anti-£. coli IgG antibodies in serum were higher when Freund's complete (FCA) or incomplete adjuvant (FIA) was administered than that without adjuvant. Production of antibodies recognizing E. coli cells and their lipopolysaccharide was enhanced by FIA, while both FIA and FCA enhanced production of antibodies recognizing outer membrane components. In contrast, serum IgM antibody levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…There have been other reports on the determination of the total IgY concentration in the egg yolk of immunized chicken, where the values differed ranging from 8 to 25 mg/ml. These differences are likely to result from the various methods to isolate and measure IgY since the total IgY concentrations were independent of the species of chicken, the nature of immunogen, and the types of adjuvant used [4,9,19,[21][22][23]. The lyophilized WSF, which was prepared by the freezedrying for a concentrated form, showed a decrease in IgY purity by 17% compared to that of the WSF.…”
Section: Discussionmentioning
confidence: 99%
“…There have been other reports on the determination of the total IgY concentration in the egg yolk of immunized chicken, where the values differed ranging from 8 to 25 mg/ml. These differences are likely to result from the various methods to isolate and measure IgY since the total IgY concentrations were independent of the species of chicken, the nature of immunogen, and the types of adjuvant used [4,9,19,[21][22][23]. The lyophilized WSF, which was prepared by the freezedrying for a concentrated form, showed a decrease in IgY purity by 17% compared to that of the WSF.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators inject the Ag with an oil-emulsion adjuvant in the breast muscle or leg muscle. For some Ags, Freund's incomplete adjuvant may be as effective as FCA (Shimizu et al, 1989). Immunostimulators that are effective in the chicken are different from those of many mammals.…”
Section: Route Of Injection and Number Of Injection Sitesmentioning
confidence: 99%
“…However, in this study, FIA alone induced a higher antibody activity against the S. aureus antigen than a combination of FCA/FIA. Shimizu et al (1989) reported a similar result in preparation of anti- E. coli IgY, in which the presence of mycobacteria components in FCA with bacterial antigen suppressed the induction of specific IgY, even when FCA was used only at the first injection, followed by FIA for the boosting immunization. Therefore, emulsion composed of bacterial antigens with oil-based adjuvants, such as FIA, enhances specific IgY activity against bacterial antigens, probably through slowly releasing the antigen in the hen's muscle.…”
Section: Discussionmentioning
confidence: 72%